Roles of intrinsic and acquired resistance determinants in multidrug-resistant clinical Pseudomonas aeruginosa in Bangladesh (Bangladesh Journal of Medical Science, 2023)
Introduction: Pseudomonas aeruginosa is an ESKAPE (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, P. aeruginosa, and Enterobacter spp.) pathogen and one of the leading etiologies in multiple nosocomial infections. Treatment of P. aeruginosa is becoming increasingly difficult due to its ever-increasing antibiotic resistance trends. This study investigated clinical multidrug resistance (MDR) P. aeruginosa (MDR-PA), their intrinsic resistance determinants, including the presence of chromosomal AmpC β-lactamase (Ampicillinase), decreased expression of outer membrane porin protein OprD and selected acquired β-lactamase resistance genes.Methods: Out of 238 clinical specimens, including urines from urinary tract-infected patients, wound swabs, burn swabs, and catheter aspirates, were collected from two major hospitals in Savar, Dhaka, Bangladesh. Samples were inoculated with Cetrimide agar to isolate presumptive P. aeruginosa. Bacteria were identified by cultural, biochemical characterization, 16S rDNA sequencing, and phylogenetic analysis. Virulence-associated genes of P. aeruginosa, namely, toxA, lasB, and plcH, were identified by polymerase chain reaction (PCR). Antibiotic susceptibilities of the isolates were investigated against ten antibiotics belonging to seven groups by disc-diffusion method followed by a selected minimum inhibitory concentration (MIC) assay. Phenotypic expression of Metallo-β-lactamases (MBLs) production was checked by the double disc synergistic test selectively among the imipenem-resistant isolates. Acquisition of β-lactam resistance trait was examined by PCR detection of bla-genes variants. Mutational loss of the OprD was analyzed by PCR to investigate intrinsic resistance determinants. Phenotypic overexpression of chromosomal AmpC was assayed with the identification of the AmpC gene by PCR. The expression level of OprD was assessed by real-time quantitative PCR (RT-qPCR).Results: Fifty-three P. aeruginosa was identified, with an overall isolation of 22.3% (53/238), where urine remains the most prevalent source. Virulence genes toxA, lasB, and plcH were identified in the isolates of 92.4%, 96.2%, and 94.3%. The highest phenotypic antimicrobial resistance was observed against ampicillin and ceftriaxone (100%), followed by cefotaxime (96%), tetracycline (89%), azithromycin (72%), imipenem (31%), ciprofloxacin (29%), levofloxacin (29%), gentamycin (27%) and ceftazidime (14%). The antibiogram pattern revealed 85% of isolates as multidrug-resistant, while 12% were considered extensively drug-resistant (XDR)-P. aeruginosa. The carriage of β-lactamase genes blaTEM, blaSHV, and blaOXA was detected in 4%, 2%, and 2% cephalosporin-resistant isolates, respectively. Double disc synergistic test revealed 87% of imipenem-resistant isolates expressing MBL-mediated resistance phenomenon. All seven ceftazidime-resistant isolates showed the presence of the AmpC gene with phenotypic overproduction of the AmpC enzyme, indicating AmpC-mediated ceftazidime resistance. Mutational loss of OprD was observed in 12% of phenotypically multidrug-resistant isolates, and RT-qPCR analysis revealed reduced expression of OprD porin protein at various levels in the outer membrane of multidrug-resistant isolates.Conclusions: This study depicts the high prevalence of MDR-PA in clinical specimens in Bangladesh. The identified intrinsic and acquired antimicrobial resistance determinants play synergistic roles in emerging MDR-PA.Bangladesh Journal of Medical Science Vol. 22 No. 03 July’23 Page : 489-507